Nephrotic syndrome disease activity is proportional to its associated hypercoagulopathy. Issue 201 (May 2021) - Waller, Amanda P.; Troost, Jonathan P.; Parikh, Samir V.; Wolfgang, Katelyn J.; Rovin, Brad H.; Nieman, Marvin T.; Smoyer, William E.; Kretzler, Matthias; Kerlin, Bryce A.; ,
Abstract: Introduction: Nephrotic syndrome (NS) is associated with an acquired hypercoagulopathy that drives its strong predilection for life-threatening thrombosis. We previously demonstrated that hypercoagulopathy is proportional to NS disease severity in animal models. Therefore, hypercoagulopathy and disease severity may inform thrombosis risk and better guide therapeutic decision making. The objective of this study was thus to establish the relationship between disease severity and hypercoagulopathy in human NS. Materials and methods: Thrombin generation assays (TGA) were performed on biorepository plasma samples from a prospective longitudinal NS cohort study. TGA was also determined on a separate cohort of incident NS patients. Multivariable regression was used to build NS-hypercoagulopathy relationship models. Results: Endogenous thrombin potential (ETP) was the TGA parameter most strongly correlated with NS severity and was proportional to conventional measures of NS disease activity including proteinuria, hypercholesterolemia, and hypoalbuminemia. The overall disease activity model was well correlated with ETP ( R 2 = 0.38). The relationship with disease activity was confirmed in the second cohort. These models further revealed that ETP is related to disease activity in a manner dependent on remission status. Conclusion: Consistent with our previously reported animal model observations, we found that the combination of proteinuria, hypercholesterolemia, and hypoalbuminemia correlated with ETP-defined hypercoagulopathy. Hypercoagulopathy improved significantly with partial or complete NS remission. These data are expected to inform studies designed to stratify thrombotic risk for patients with NS. Graphical abstract: Unlabelled Image Highlights: Nephrotic syndrome acquired hypercoagulopathy drives thrombotic complications. Hypercoagulopathy is proportional to nephrotic disease activity. Hypercoagulopathy improves with partial or complete remission of nephrosis. Nephrotic activity biomarkers may guide thromboprophylaxis use in the future.